PF.51 Expectant Management of Prenatally Diagnosed Fetal Aneuploidy. (26th April 2013) - Burke, N; Flood, K; Said, S; Muellers, S; Breathnach, F; Barry, C; Geary, M; Malone, F
Abstract : It is essential to counsel patients about all options following the prenatal diagnosis of fetal aneuploidy (FA). We sought to ascertain the prenatal course and pregnancy outcomes in those with a prenatal diagnosis of fetal aneuploidy and were managed expectantly. Prenatally diagnosed cases of FA were identified from the anomaly register between 2005 and 2011. The indication for diagnostic testing, the ultrasound findings and subsequent pregnancy outcomes were analysed. There were 212 cases of prenatally diagnosed FA registered on the database during the study time period. There were 84 (39%) cases of expectant management. The indication for invasive testing included; markers at fetal anatomical survey (n = 49); cystic hygroma (n = 21); high risk FTS (n = 11) and maternal request (n = 3). Second trimester ultrasound abnormalities detected included; Multiple abnormalities 36%, cardiovascular 19%, central nervous system 19%, cystic hygroma 9% and others 17%. Cases of Trisomy 18 and 13 were more likely to be managed expectantly than T21, OR 0.14 (95% CI 0.08–0.25 p < 0.0001). Intra-uterine death (IUD) occurred in 40 (48%) cases, late miscarriage in 13 (15%), early neonatal death in 14 (17%) and 17 (20%) infants were alive at six week follow up. The mean gestational age at delivery was 31 weeks. This study provides much needed data about the expectant management of affected pregnancies. Important information includes the high rate of IUD and preterm delivery. We found that patients in our cohort were more likely to continue the pregnancy with a lethal diagnoses of T13 and 18 compared to T21.